Social security incentives, human capital investment and mobility of labor - Panu Poutvaara (Institute for the Study of Labor (IZA), 2005)
Migration between countries with earnings-related and flat-rate pay-as-you-go social security systems may change human capital investments in both countries. The possibility of emigration boosts investments in human capital in the country with flat-rate benefits. Correspondingly, those expecting to migrate from the country with earnings-related benefits to a country with flat-rate benefits may reduce their investment in education. With suitably planned transfers between the two countries, allowing for migration may generate a Pareto-improvement for all current and future generations. Without transfers, either country may be unable to pay for promised benefits when labor becomes mobile.
Keywords: H55; I2; F22; 330; social security; education; migration; earnings-related and flat-rate pensions; Soziale Sicherung; Rentenfinanzierung; Bildungsinvestition; Internationale Arbeitsmobilität; Theorie